Isolation of methicillin-resistant coagulase-negative staphylococci from chickens. - Kawano, J (1996)
Methicillin-resistant coagulase-negative staphylococci were isolated from the nares and skin of 1- to 8-week-old healthy chickens in three flocks from a farm. Isolation of methicillin-resistant coagulase-negative staphylococci was positive for 72 (25.7%) of the 280 chickens tested, with the frequency varying from 2.2 to 100% according to flock. A total of 45 appropriate isolates were selected and subjected to identification. Of the 45 methicillin-resistant coagulase-negative staphylococcal isolates selected, 37 were identified as Staphylococcus sciuri, 5 were identified as Staphylococcus epidermidis, and 3 were identified as Staphylococcus saprophyticus. The distribution of the species was different among the flocks. Comparative analysis of the SmaI-digested chromosomal DNA by pulsed-field gel electrophoresis revealed that the isolates could have originated from a single clone of each of S. sciuri and S. saprophyticus and three clones of S. epidermidis. By two methods based on the PCR technique, the mecA gene was detected in all five representative isolates of each methicillin-resistant coagulase-negative staphylococcal clone. The nucleotide sequence of a PCR fragment obtained from an isolate of S. sciuri was completely identical to the corresponding region of mecA genes reported in human methicillin-resistant Staphylococcus aureus isolates and Staphylococcus epidermidis isolates. The representative methicillin-resistant coagulase-negative staphylococcal isolates were resistant to many beta-lactam antibiotics, and some isolates were also resistant to macrolide and aminoglycoside antibiotics. This is the first evidence of the existence of methicillin-resistant coagulase-negative staphylococci from animals possessing the mecA gene.